Gypsum batten extruded by semi-dry method and production process of gypsum batten
Through the semi-dry extrusion process and specific raw material ratio, the problems of long drying and drying time of gypsum products during pouring method are solved, and the water paste ratio is reduced, rapid absolute drying and performance improvement is achieved, and gypsum bars are improved. comprehensive performance.
Patent Information
- Application Number
- CN202411334626.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
In the production of existing gypsum building materials, gypsum products manufactured by the casting method contain a large amount of free water and adhesion water, resulting in a long drying and drying time, and a large amount of raw materials, which affects the performance of the product.
The semi-dry extrusion process is adopted to achieve the water paste ratio through the specific ratio of gypsum, water, retarder, water reducing agent, defoaming agent and reuse fiber, combined with tower double stirring conveying and dual-shaft extruder. Reduce it to below 30%, quickly reach the absolute dry state, and improve the comprehensive performance of gypsum strips by optimizing raw material ratio.
It reduces drying and drying time, improves the apparent density, flexural strength and compressive strength of the gypsum strips, directly enters the sales stage, and achieves higher performance with less raw material usage.
Smart Images

Figure CN119217505A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gypsum building material production, and in particular relates to a semi-dry extruded gypsum strip board and a production process thereof. Background Art
[0002] At present, most gypsum building materials are manufactured by casting method, and the water content of gypsum is relatively large. The water required for hemihydrate gypsum to react with water to form dihydrate gypsum is only 18% of the total weight of hemihydrate gypsum, while the water content of gypsum in casting method is currently above 40%, which results in a large amount of free water and attached water in the newly manufactured casting gypsum products, which require a long time of drying and drying. Summary of the invention
[0003] In order to solve the problems in the prior art, the present invention provides a semi-dry extruded gypsum strip board and its production process, which can achieve a water-to-cement ratio of less than 30%, and the free water and attached water can quickly reach an absolutely dry state after medium-temperature drying, and directly enter the sales link, and with less raw material consumption, the purpose of improving the comprehensive performance of the gypsum strip board is achieved.
[0004] The present invention solves the technical problem by adopting the following technical solutions:
[0005] The present invention aims to provide a semi-dry extruded gypsum strip board, comprising the following raw materials: gypsum, water, retarder, water reducing agent, defoamer and recycled fiber.
[0006] Furthermore, the mass ratio of gypsum, water, retarder, water reducing agent, defoamer and recycled fiber is 100:30:0.03:0.5:0.3:8.
[0007] Furthermore, the retarder is one of citric acid, CBMA retarder and tartaric acid.
[0008] Furthermore, the water reducing agent is one of polycarboxylic acid 405s, nylon UNF5 and melamine SM.
[0009] Furthermore, the defoaming agent is Longhu 803 or Huashengyuan DL-004.
[0010] Further, it includes gypsum, water, citric acid, polycarboxylic acid 405s, Longhu 803 and recycled fiber in a mass ratio of 100:30:0.03:0.5:0.3:8.
[0011] Further, a production process of a semi-dry extruded gypsum board comprises the following steps:
[0012] S1: premix the recycled fiber and gypsum according to a certain proportion, and premix the defoamer, water reducing agent and retarder according to a certain proportion;
[0013] S2: Add the premix of recycled fiber and gypsum, the premix of defoamer, water reducer and retarder, and deionized water into the main barrel and stir;
[0014] S3: The gypsum slurry stirred evenly in S2 enters the horizontal feeding screw through the main barrel;
[0015] S4: The gypsum slurry then reaches the tower-type double stirring and conveying mechanism through the horizontal feeding screw;
[0016] S5: The gypsum slurry is extruded from the twin-shaft extruder via a tower-type double-stirring conveying mechanism;
[0017] S6: The extruded sheet is subjected to a chain-type secondary molding mechanism to adjust the surface flatness and tenon and mortise flatness of the sheet;
[0018] S7: After cutting and drying, it reaches an absolutely dry state.
[0019] Furthermore, the mixing time of the recycled fiber and gypsum premixed in proportion is 3-8 minutes, and the mixing time of the defoamer, water reducing agent and retarder premixed in proportion is 3-8 minutes.
[0020] Furthermore, the raw materials in S2 are stirred in the main barrel for 15-20 minutes until the consistency of the gypsum slurry is 180 mm.
[0021] Furthermore, the gypsum mortar unit emptying time is 20-30 minutes.
[0022] Compared with the prior art, the beneficial technical effects of the present invention are:
[0023] 1. The present invention extrude gypsum through a semi-dry method, and the water-to-gypsum ratio is below 30%, which reduces the time of airing and drying and the use of a large number of storage yards. The free water and the attached water quickly reach an absolutely dry state after medium-temperature drying and directly enter the sales link.
[0024] 2. The present invention finds out the best ratio of raw materials such as admixtures by cooperating with the gypsum semi-dry extrusion process, and further improves the comprehensive performance of gypsum strip board with less dosage, reaching an apparent density of 1.44g / cm3, a flexural strength of 6.6Mpa, and a compressive strength of 22.85MPa.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above contents of the present invention and its objectives, features and advantages more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a simplified production process flow diagram of a gypsum board extruded by a semi-dry method. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0028] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0029] A semi-dry extruded gypsum strip board comprises the following raw materials: gypsum, water, retarder, water reducer, defoamer and recycled fiber. The semi-dry extruded gypsum strip board is subjected to relevant consistency, initial setting time, final setting time and other tests, so as to adjust the dosage of each component in the formula raw materials and the specific raw materials.
[0030] Experimental Example 1
[0031] The test of the retarder formula is shown in Table 1. The gypsum specimens mixed with citric acid could not be demolded after 2 hours, so the citric acid group had a natural strength of 4 hours; the other groups had a natural strength of 2 hours. As the amount of CBMA retarder increased, the consistency gradually increased and the setting time gradually prolonged. The flexural and compressive strengths gradually decreased, and the apparent density before failure was 1.64-1.69g / cm 3 With the increase of tartaric acid content, the consistency and setting time remain basically unchanged. The retarding effect is not obvious, and the flexural and compressive strengths gradually decrease, and the apparent density before failure remains basically unchanged. With the increase of citric acid content, the consistency increases significantly and the setting time is also greatly extended. The retarding effect is the best.
[0032] Table 1
[0033]
[0034] The test results of the three retarders above show that at a water-to-cement ratio of 0.6, citric acid has the best effect among the three retarders, followed by CBMA retarder, and tartaric acid has no retarding effect. The best dosage of citric acid is 0.2‰, and the best dosage of CBMA retarder is 0.5%; because when the amount of citric acid added increases, it will seriously affect the habits of dihydrate gypsum crystals, making it impossible for crystals to grow into each other and condense; even if it is fully hydrated, it will prevent the gypsum slurry from condensing, resulting in a decrease in the strength of gypsum products, so the best dosage of citric acid is 0.2‰.
[0035] Experimental Example 2
[0036] The test of water reducing agent formula is shown in Table 2. With the increase of UNF5 dosage, the water-paste ratio gradually decreases, the water reduction effect becomes more and more obvious, but the setting time gradually accelerates. The flexural and compressive strengths are higher than those without admixture. With the increase of SM dosage, the water-paste ratio gradually decreases, the water reduction effect becomes more obvious, and the setting time is slightly faster. The flexural and compressive strengths gradually increase, with the largest increase between 7‰-9‰. With the increase of 405S dosage, the water-paste ratio gradually decreases significantly, the water reduction effect becomes more obvious, and the setting time gradually prolongs.
[0037] Table 2
[0038]
[0039] The above test results of water reducer show that:
[0040] When the dosage is 3‰, the water-paste ratios of UNF5, SM, and 405S are 0.52, 0.54, and 0.44 respectively;
[0041] When the dosage is 5‰, the water-paste ratios of UNF5, SM, and 405S are 0.51, 0.51, and 0.30 respectively;
[0042] When the dosage is 7‰, the water-paste ratios of UNF5, SM, and 405S are 0.49, 0.50, and 0.30 respectively;
[0043] When the dosage is 9‰, the water-paste ratios of UNF5 and SM are 0.48 and 0.48 respectively;
[0044] The preferred dosage of 405S is 5‰; the dosage of UNF5 is 3‰; and the dosage of SM is 9‰. The reason is that the gypsum slurry in the main barrel must have a certain consistency to smoothly enter the horizontal feeding screw and move smoothly in the horizontal feeding screw and tower double stirring and conveying mechanism. During the extrusion stage, as dihydrate gypsum is formed, the consistency of the gypsum slurry increases and reaches the initial setting state for shaping. When the dosage of 405S is 5‰, the initial setting time is easy to adjust, and the amount of water reducer is small.
[0045] Experimental Example 3
[0046] The defoamer formula test is shown in Table 3. As the dosage of defoamer Longhu 803 increases, the consistency remains basically unchanged, the setting time is slightly extended, and the flexural and compressive strengths increase, with the largest increase between 2‰ and 3‰. As the dosage of defoamer Huashengyuan DL-004 increases, the consistency remains basically unchanged, the setting time is slightly extended, and the flexural and compressive strengths increase slightly.
[0047] Table 3
[0048]
[0049] The above test results of defoamers show that Longhu 803 has higher two-hour flexural strength and compressive strength than Huashengyuan DL-004, and most defoamers contain silicate components. If too much is added, it will affect the self-leveling effect of the surface of gypsum building materials and even produce bubbles. Among the two defoamers, the water-to-paste ratio is 0.6, Longhu 803 has the best effect, and the best dosage is 3‰.
[0050] Experimental Example 4
[0051] The gypsum compounding ratio was tested, and the results are shown in Table 4. When the water-to-cement ratio is 0.3, the dosage of citric acid retarder is 0.3‰, the dosage of polycarboxylic acid 405s is 5‰, and the dosage of Longhu 803 is 3‰, it is more in line with the actual production conditions of semi-dry gypsum board.
[0052] Table 4
[0053]
[0054] The test results of the compounding ratio of the three admixtures show that the interaction between the three admixtures affects the initial setting time and the final setting time. By fixing the dosage of water reducer and defoamer and adjusting the dosage of retarder, the optimal ratio is 0.3‰ of citric acid retarder, 5‰ of polycarboxylic acid 405s and 3‰ of Longhu 803.
[0055] Experimental Example 5
[0056] The fiber dosage formula of gypsum was tested, as shown in Table 5 below. The fiber dosage was tested according to the optimal compound ratio. It was found that when the fiber dosage was 8%, the flexural strength and compressive strength increased fastest, and the dosage economy was the most reasonable.
[0057] Table 5
[0058]
[0059] The test results of the above gypsum fiber dosage formula show that when the water-to-cement ratio is 0.3, the dosage of citric acid retarder is 0.3‰, the dosage of polycarboxylic acid 405s is 5‰, the dosage of Longhu 803 is 3‰, and the recycled fiber is 8%, the flexural and compressive strengths increase significantly.
[0060] Example 1
[0061] A production process of semi-dry extruded gypsum strip board comprises the following steps:
[0062] S1: The recycled fiber from wind turbine blades and β-gypsum are premixed and stirred in proportion for 5 minutes; the admixtures including defoamer, water reducer and retarder are premixed and stirred for 5 minutes; the materials are in a dry state at this stage, and the stirring time is not included in the calculation of the initial setting and final setting time.
[0063] S2: The main barrel includes three material inlets. Recycled fiber and gypsum premix, admixture premix, and deionized water are added to the main barrel in proportion. According to test measurements, the gypsum slurry is easier to form when the consistency is 180. To reach the relevant consistency, the main barrel must be stirred for at least 15 minutes on the premise that the main barrel stirring motor matches the barrel material. To ensure that the slurry is fully mixed and the consistency meets the standard, the main barrel stirring is set to about 18 minutes.
[0064] S3: The evenly stirred gypsum slurry enters the horizontal feeding screw through the solenoid valve at the bottom of the main barrel. The horizontal feeding screw connects the two main barrels and is switched through the solenoid valve to complete uninterrupted continuous production. The emptying time at this stage is about 3 minutes.
[0065] S4: The gypsum slurry reaches the tower-type double-stirring and conveying mechanism through the horizontal feeding screw. This mechanism uses the thrust generated by the spiral mechanism to enable the gypsum slurry to smoothly enter the twin-shaft extruder. The emptying time of the tower-type double-stirring and conveying mechanism is about 3 minutes.
[0066] S5: The gypsum slurry reaches the twin-shaft extruder through the tower double-stirring and conveying mechanism. The twin-shaft extruder performs secondary compression and extrusion through the twin-shaft extrusion and output material diameter reducing port. At this time, the gypsum slurry should be in the initial setting state, and the emptying time of the twin-shaft extrusion mechanism is about 4 minutes.
[0067] S6: The extruded sheet is passed through a chain secondary molding mechanism to adjust the surface flatness and tenon and mortise flatness of the sheet.
[0068] S7: After cutting and drying, it reaches an absolutely dry state.
[0069] Table 6 below shows the amounts of various raw materials used and the actual measured results of the products in this Example 1.
[0070] Table 6
[0071]
[0072] The emptying time of unit dry material in the semi-dry process equipment is about 15 minutes. Considering the influence of the consistency of gypsum mortar on emptying, the emptying time of unit gypsum mortar with standard consistency is about 20 minutes or more. The above formula of the present invention is used for testing in actual working conditions, and the emptying time of unit gypsum mortar in the equipment is measured to be 26 minutes. Therefore, the current formula can basically meet the requirements of gypsum mortar reaching the initial setting and shaping stage in the twin-shaft extruder by adjusting the motor speed of the main barrel, horizontal feeding screw, and tower double stirring and conveying mechanism.
[0073] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0074] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A semi-dry extruded gypsum board, characterized in that: The raw materials include gypsum, water, retarder, water reducing agent, defoaming agent and recycled fiber.
2. A semi-dry extruded gypsum board as claimed in claim 1, characterized in that: The mass ratio of gypsum, water, retarder, water reducer, defoamer and recycled fiber is 100:30:0.03:0.5:0.3:
8.
3. A semi-dry extruded gypsum board as claimed in claim 2, characterized in that: The retarder is one of citric acid, CBMA retarder and tartaric acid.
4. A semi-dry extruded gypsum board as claimed in claim 3, characterized in that: The water reducing agent is one of polycarboxylic acid 405s, nylon UNF5 and melamine SM.
5. A semi-dry extruded gypsum board as claimed in claim 4, characterized in that: The defoaming agent used is Longhu 803 or Huashengyuan DL-004.
6. A semi-dry extruded gypsum board as claimed in claim 5, characterized in that: It comprises gypsum, water, citric acid, polycarboxylic acid 405s, Longhu 803 and recycled fiber in a mass ratio of 100:30:0.03:0.5:0.3:
8.
7. A process for producing a gypsum board by semi-dry extrusion as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1: premix the recycled fiber and gypsum according to a certain proportion, and premix the defoamer, water reducing agent and retarder according to a certain proportion; S2: Add the premix of recycled fiber and gypsum, the premix of defoamer, water reducer and retarder, and deionized water into the main barrel and stir; S3: The gypsum slurry stirred evenly in S2 enters the horizontal feeding screw through the main barrel; S4: The gypsum slurry then reaches the tower-type double stirring and conveying mechanism through the horizontal feeding screw; S5: The gypsum slurry is extruded from the twin-shaft extruder via a tower-type double-stirring conveying mechanism; S6: The extruded sheet is subjected to a chain-type secondary molding mechanism to adjust the surface flatness and tenon and mortise flatness of the sheet; S7: After cutting and drying, it reaches an absolutely dry state.
8. A process for producing a semi-dry extruded gypsum board as claimed in claim 1, characterized in that: The mixing time of the recycled fiber and gypsum premixed in proportion is 3-8 minutes, and the mixing time of the defoamer, water reducer and retarder premixed in proportion is 3-8 minutes.
9. A process for producing a semi-dry extruded gypsum board as claimed in claim 1, characterized in that: The raw materials in S2 are stirred in the main barrel for 15-20 minutes until the consistency of the gypsum slurry is 180 mm.
10. A process for producing a semi-dry extruded gypsum board according to claim 1, characterized in that: The emptying time of the gypsum mortar unit is 20-30 minutes.
